Sineol dalam Minyak Kayu Putih sebagai Pelangsing Aromaterapi - Irmanida Batubara; Irma Herawati Suparto; Fiqa Annisa Rakhmatika (Jurnal Jamu Indonesia, 2016)
Cajuput is one of plants containing essential oil with cineole as a major component. This aim of study is to separate cineole in cajuput oil and to analyze its potency as slimming aromatherapy through in vivo assay. The essential oil was fractionated by column chromatography resulting 23 fraction (F1-F23). Cajuput oil, cineole, and F9 were analyzed by gas chromatograph-mass spectrometer, and the slimming aromatherapy potency was studied on white adult male Sprague-Dawley rats. Inhalation result of cineole showed that the average body weight of rats after 5 weeks treatment period was lower than that of the normal and the control groups which consumed high cholesterol feed. In conclusion, cineole is a compound that is potential in slimming aromatherapy.